Proceedings of the 51st Annual ACM SIGACT Symposium on Theory of Computing 2019
DOI: 10.1145/3313276.3316312
|View full text |Cite
|
Sign up to set email alerts
|

Private PAC learning implies finite Littlestone dimension

Abstract: We show that every approximately differentially private learning algorithm (possibly improper) for a class H with Littlestone dimension d requires Ω log * (d) examples. As a corollary it follows that the class of thresholds over N can not be learned in a private manner; this resolves open questions due to [Bun et al., 2015, Feldman andXiao, 2015]. We leave as an open question whether every class with a finite Littlestone dimension can be learned by an approximately differentially private algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The following well‐known result, which appears in , relates the degree of stability of a graph to its tree bound (see also [, Appendix B] for another, recent exposition on the proof). Theorem For each integer k there exists d=dfalse(kfalse)<2k+22 such that if normalΓ is a k‐stable graph, then its tree bound d(Γ) is at most d.…”
Section: Building a Tree In The Absence Of Efficient Regularitymentioning
confidence: 99%
See 1 more Smart Citation
“…The following well‐known result, which appears in , relates the degree of stability of a graph to its tree bound (see also [, Appendix B] for another, recent exposition on the proof). Theorem For each integer k there exists d=dfalse(kfalse)<2k+22 such that if normalΓ is a k‐stable graph, then its tree bound d(Γ) is at most d.…”
Section: Building a Tree In The Absence Of Efficient Regularitymentioning
confidence: 99%
“…The following well-known result, which appears in [17], relates the degree of stability of a graph to its tree bound (see also [2,Appendix B] for another, recent exposition on the proof).…”
Section: Building a Tree In The Absence Of Efficient Regularitymentioning
confidence: 99%
“…For approximate differential privacy, the current understanding is more limited. Recent results established that the class of one-dimensional thresholds over a domain X ⊆ R requires sample complexity between Ω(log * |X|) and 2 O(log * |X|) (Beimel et al [2013b], Bun et al [2015], Bun [2016], Alon et al [2018]). On the one hand, these results establish a separation between what can be learned with or without privacy, as they imply that privately learning one-dimensional thresholds over an infinite domain is impossible.…”
Section: Introductionmentioning
confidence: 99%
“…(A threshold function is a binary function that evaluates to 1 on some prefix of the domain. 1 ) The goal is to generalize the training data into a hypothesis h that predicts the labels of unseen examples. In this paper we study this problem under the constraint of differential privacy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Bun et al [5] showed a lower bound of Ω(log * |X|) on the sample complexity of every approximateprivate learner for thresholds that outputs a hypothesis that is itself a threshold function (such a learner is called proper). Recently, Alon et al [1] showed that a lower bound of Ω(log * |X|) holds even for improper learners, i.e., for learners whose output hypothesis is not restricted to being a threshold function. To summarize, our current understanding of the task of privately learning thresholds places its sample complexity somewhere between Ω(log * |X|) and Õ 2 log * |X| , a gap which is exponential in log * |X|, where at least three different algorithms are known with sample complexity 2 O(log * |X|) .…”
Section: Introductionmentioning
confidence: 99%